GE_GERICHTE A/3861/2012 vom 4. November 2013 - GE Cour de justice (2013)
; IMPÔT ; DÉDUCTION POUR FRAIS D'ENTRETIEN D'IMMEUBLE ; COPROPRIÉTÉ | LIFD.32.al2; LIPP-V.6.al4; LIFD.33.al1.leta; LIPP-V.6.al1